Hydroacoustic estimation of fish biomass in the Gulf of Nicoya, Costa Rica - Hedgepeth, John (2000)
A stratified sampling design Was used for a hydroacoustic survey of the inner parts of the Gulf of Nicoya in 1987 and 1 988. The bottom topography of the inner Gulf was modeled by introducing the concept of a topographical basin model, as the basis for the projection of the sample survey estimates to the entire inner gulf. The bottom depth contours and volumes for the basin model'were constructed from nautical charts. The estimates of sample abundance were made for the fish in the inner Gulf using the acoustic methods, EMS (Expectation Maxirnization and S moothing) and echo integration. The estimates of population were made by the multiplication of the topographic model's estimate of water volume and a model of fish density dependent on bottom depth. The results showed a general decrease in fish density biomass with bottom depth, and a simultaneous tendency for maximum concentrations over bottom depths of about four meters. The four meter bottom depth ¡neludes a broad expanse of the inner Gulf located south of Isla Chira. Overall estimates of volumetric density (0.269 fishlm3) and of area! densities ( 1 .88 fishlm2) are comparable to other estuarine shallow water environments.